Influence of upper lip form on incisal display of maxillary central incisors at repose - Lamichhane, Samjhana; Pradhan Joshi, Sarita; Shrestha, Pragya; Sah, Sanjay; Verma, Anand; Mishra, Manish Kumar (Journal of Nepalese Prosthodontic Society, 2026)
Introduction: Knowledge of various factors that can influence the upper incisal display is very crucial in order to provide more aesthetically driven restorations and prosthesis. The purpose of this study was to evaluate the influence of upper lip form on incisal display of maxillary central incisors at repose. After correctly identifying the lip form and its relation with incisal display, one can provide more aesthetically pleasing restorations and prosthetic rehabilitations to their patients. Methods: This is a cross-sectional observational study done at Department of Prosthodontic, NAMS, Bir Hospital. The study subjects included 170 volunteers (87 males and 83 females) aged 18-35 years. Standardized photographs were taken with DSLR camera, and measurements were performed using the keynote application. Lips were classified as straight, moderate, and high. Maxillary incisal display at repose was measured. The independent sample t-test was used to assess the means of incisal display. Results: The results suggested that the moderate lip form was the most prevalent type. The average amount of incisal display was slightly greater in females for each lip form compared to males. However, the finding was not statically significant. (p-value=0.513) Conclusion: The moderate lip form, which accounts for 60% of each group, was the most common lip form in both genders. There was a greater incisal display in females in all the lip forms. The influence of lip form on incisal display and sexual dimorphism was clinically obvious, but the values were not statistically significant.